Last order sa Penguin - Martinez, Chris (The University of the Philippines Press, 2003)
Last Order Sa Penguin (roughly translated for the benefit of my international readers: Last Order at the Penguin Cafe) is a two-act play about five friends nearing their thirties: the cheerfully gay Tuxqs, the problematic Harlene, the sex addict Tess, the social climbing Dyna, and the druggie Mario, who all meet up at the Penguin Cafe in Malate.